EMI Troubleshooting cookbook for product designers - André, Patrick G.; Wyatt, Kenneth (Product development engineer) (Scitech Publishing, an imprint of the IET, 2014)
This is a one-stop guide that will help engineers and technicians who have products which fail to meet EMI/EMC regulatory standards. It provides "recipes" of simple, easily implemented, and inexpensive troubleshooting tools or aids that can be built by the engineer or the technician. Written in a very simple style requiring only minimal electromagnetic theory and math, the "cookbook" will teach the engineer and technician to develop a "process" for troubleshooting--making it a straight-forward approach to solving what may seem like a rather complicated problem. Real-world stories are used to further illustrate both the concepts put forth in the book and the thinking process required when troubleshooting EMI problems. -- Edited summary from book.
Keywords: Electromagnetic interference.; Electromagnetic compatibility.; Shielding (Electricity) -- Standards.; elektronické knihy; electronic books